La comunicación externa para el posicionamiento de la imagen corporativa del Instituto Provincial de Asistencia Social de Bolívar (IPASB) Guaranda – Bolívar, periodo 2023 - Romero Pozo, Lady Tatiana (2024)
This thesis is based on the study of corporate image and the importance of external communication in the Provincial Institute of Social Assistance of Bolívar (IPASB), whose third specific objective is to develop an external communication plan to position the corporate image of this organization, by disseminating information on the social networks of Facebook, Instagram and Tik Tok. For this purpose, theoretical, conceptual, scientific and legal investigations were carried out that support the viability of this work. In addition, through an investigative analysis, it was possible to collect information from repositories, articles, scientific journals that contain relevant elements such as previous research related to the variables of the topic, as well as the use of methods, techniques and instruments of data collection, applied to through surveys and interviews, necessary contributions that help advance it. All this in order to propose good management of the corporate image, based on the findings and analysis of the study, a feasible proposal is made, which focuses on the objectives, activities, strategies and action plans as a starting point for stimulate social change, achieve the development and progress of the canton; In this way, give value to the proposed communicative proposal, which will be the main axis for its development throughout this research work.